Nutritional response of a coccolithophore to changing pH and temperature. Issue 10 (27th August 2022) - Johnson, Roberta; Langer, Gerald; Rossi, Sergio; Probert, Ian; Mammone, Marta; Ziveri, Patrizia
Abstract: Coccolithophores are a calcifying unicellular phytoplankton group that are at the base of the marine food web, and their lipid content provides a source of energy to consumers. Coccolithophores are vulnerable to ocean acidification and warming, therefore it is critical to establish the effects of climate change on these significant marine primary producers, and determine potential consequences that these changes can have on their consumers. Here, we quantified the impact of changes in pH and temperature on the nutritional condition (lipid content, particulate organic carbon/nitrogen), growth rate, and morphology of the most abundant living coccolithophore species, Emiliania huxleyi . We used a regression type approach with nine pH levels (ranging from 7.66 to 8.44) and two temperatures (15°C and 20°C). Lipid production was greater under reduced pH, and growth rates were distinctly lower at 15°C than at 20°C. The production potential of lipids, which estimates the availability of lipids to consumers, increased under 20°C, but decreased under low pH. The results indicate that, while consumers will benefit energetically under ocean warming, this benefit will be mitigated by ocean acidification. The carbon to nitrogen ratio was higher at 20°C and low pH, indicating that the nutritional quality of coccolithophores for consumers will decline under climate change. The impact of low pH on the structural integrity of the coccosphere may also mean that coccolithophores are easier to digest for consumers. Many responses suggest cellular stress, indicating that increases in temperature and reductions in pH may have a negative impact on the ecophysiology of coccolithophores.